Bariatric surgery in severely obese adolescents – a single centre experience. (24th May 2012) - Sachdev, P; Makaya, T; Marven, S; Ackroyd, R; Wales, J; Wright, N
Abstract : Background: Increasing numbers of severely obese young people undergo bariatric surgery in the USA with reports of 58-73 % of excess weight lost after one year. In 2006, NICE suggested considering surgery for young people in 'exceptional circumstances'. We present 5 patients operated upon between 2005-2011 at our centre focussing on the ethical and clinical dilemmas faced when establishing a service. Case series/methods Five patients (4 male) aged 14-16 years (mean age 15.25) underwent bariatric surgery. Initial cases were discussed by the local clinical ethics committee prior to the procedures. Mean pre-operative BMI was 60.3 kg/m2 and BMI SDS + 4.3. Co-morbidities included hypertension, insulin resistance, obstructive sleep apnoea, limited mobility and psychosocial issues. All 5 patients had prior involvement with local weight management services with no success. Three of the patients had tried drug treatment with orlistat and/or sibutramine (before it was withdrawn). Two patients were referred from outside the region. Three laparoscopic gastric bypass procedures, 1 laparoscopic gastric banding (patient had a gastric balloon prior to band) and 1 laparoscopic sleeve gastrectomy was performed. No major post operative procedural complications were noted (one patient had a port-rotation) and patients were discharged home within 48 hours. Results: Mean percentage of weight loss as a percentage of total body weight at 3 months and 6 months was 11% and 13.25% respectively. Three year data for 1 patient showed 15% weight loss but disappointingly at 5 years, this has not been sustained. Mean BMI at 3 months post procedure was 53 kg/m2 and BMI SDS +4.1. Mean BMI and BMI SDS at 6 months was 51 and +4.0. Resolution of hypertension, increased physical activity and improved school attendance were some of the benefits noted. None of the patients have developed T2DM. Conclusion: Recent systematic reviews and meta-analyses suggest that bariatric surgery results in sustained and clinically significant reduction in BMI in adolescents. There were no significant changes recommended in the 2011 review of the previous NICE guidance. Short term follow up data on our cohort of patients' shows initial significant weight loss but less than would be suggested from previous data. Longer term outcomes need to be followed. The surgical option should continue to be exercised with extreme caution at specialist units and only in severely obese adolescents.